(untitled) (Acta Scientiarum. Biological Sciences, 2022)
Stingless bees are important pollinators for various plant crops. We investigated the susceptibility of Tetragonisca fiebrigi to sublethal concentrations of insecticides fipronil, malathion, and thiamethoxam (administered through contact and ingestion) by determining the LC50 values after 24 hours of exposure and analyzing changes in the activity of esterase isoenzymes and the chromatin in brain cells. The LC50 values showed that all three insecticides were highly toxic through contact and ingestion. Electrophoretic analysis revealed that the relative EST-4 (carboxylesterase) activity in T. fiebrigi was partially inhibited by malathion and fipronil ingestion. Moreover, the EST-4 band intensity was increased following high-concentration thiamethoxam (contact) exposure, indicating the increased relative activity of this isoenzyme to detoxify the compound. In the cytochemical analysis of brain cells, the critical electrolyte concentration (CEC) points for the control stingless bees and malathion ingestion-exposed and thiamethoxam-exposed (contact and ingestion) stingless bees were in the range of 0.20-0.30 M MgCl2, whereas that for malathion contact-exposed bees was 0.15 M MgCl2, indicating chromatin relaxation and suggesting an increase in gene expression. In conclusion, T. fiebrigi stingless bees are susceptible to the insecticides tested, and the parameters analyzed may be used as biomarkers to detect the presence of these compounds.